Venous Thromboembolism and Decreased Serum Albumin in Children with Acute Lymphoblastic Leukemia: A Challenge for Endothelial Homeostasis? - Paola Muggeo; Vito Michele Rosario Muggeo; Massimo Grassi; Teresa Perillo; Jessica Forte; Celeste Raguseo; Nicola Santoro (Hemato)
Background: Serum albumin is crucial for critically ill patients. To date, several reports have focused on the influence of lower albumin levels on poorer prognosis and disease outcome in different subsets of critical clinical conditions varying from sepsis, to cirrhosis, renal failure, and cancer. In the last few years, investigators reported the role of serum albumin levels in predicting the thrombotic risk in patients with nephrotic syndrome, and, in particular, the degree of hypoalbuminemia seemed to influence the risk of thromboembolism. Decreased serum albumin has been associated with the risk of venous thromboembolism and mortality in adult cancer patients after ending chemotherapy for different malignancies. Aims: We aimed to investigate the role of serum albumin in a cohort of children diagnosed as having VTE (venous thromboembolism) during their treatment for acute lymphoblastic leukemia (ALL) compared to ALL children who did not experience VTE. Methods: A nested case-control study was conducted at the Pediatric Oncology and Hematology Department, University Hospital of Bari. A total of 167 patients were diagnosed as having ALL and treated according to AIEOP-BFM ALL 2000-R2006 protocol. Among these, 12 cases of VTE were recorded and matched to 31 controls, for a total of 43 ALL patients (30 males, aged 1.2–16.6 years) enrolled in the present study. Serum albumin level was collected at diagnosis—before the start of any treatment—(time point 0) and at the moment of the VTE or corresponding time point of the protocol (time point 1). Information on inherited thrombophilia genotype were also recorded. Results: Patients presenting VTE showed a marked reduction of average albumin levels as compared to the control children: t0–t1 1.1 IC (95%) = (0.55, 1.65) vs. 0.31 IC (95%) = (0.08, 0.55); p < 0.005. Conclusions: The reduction of serum albumin levels in our cohort might be an expression of altered vascular and endothelial homeostasis, likely predisposing to VTE. This important clinical observation warrants further larger studies.